On The Production Of Comparative Structures In Child Speech - Gathercole, Virginia C. Mueller (Kansas Working Papers in Linguistics, 1979)
Two children’s spontaneous utterances containing the comparative structure are examined for their semantic content. Many comparatives are found to encode the notion ’A has property X,’ and this use is often found in reference to the presence of X to an extreme, rather than a non-extreme, extent. The uses of the comparative are analyzed in relation to the same two children’s uses of too X for ’A is (very) X’ and of simple adjectives to encode ’A is X enough.’